Music Performance Anxiety (MPA) pada Mahasiswa Universitas Nusa Cendana - Richad A. Rihi; Yeni Damayanti; Dian L. Anakaka (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Music Performance Anxiety (MPA) is a form of anxiety experienced when individuals perform their musical abilities in front of an audience. This condition may affect performance quality, concentration, and musicians’ psychological well-being. This study aimed to describe the level of Music Performance Anxiety among students of Nusa Cendana University who had experience in musical performance activities. A quantitative approach with a descriptive design was employed. A total of 96 students were recruited using a convenience sampling technique. Data were collected using the Music Performance Anxiety Scale, consisting of 15 items covering somatic and cognitive symptoms, performance context, and performance evaluation. Data were analyzed using descriptive statistics through univariate analysis. The results revealed that 53.1% of respondents were categorized as having high Music Performance Anxiety, while 46.9% were categorized as moderate, with no respondents in the low category. The mean score of 2.53 and a standard deviation of 0.502 indicate a relatively high tendency of performance anxiety among the participants. These findings suggest that student musicians remain vulnerable to psychological pressure in performance settings and highlight the importance of emotional regulation and anxiety management strategies in musical performance contexts.